2005
DOI: 10.1086/502545
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Hand Hygiene and Glove Use in a University-Affiliated Hospital

Abstract: Compliance with handwashing was low, suggesting the need for new motivational strategies such as supplying feedback regarding compliance rates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 20 publications
13
65
0
4
Order By: Relevance
“…In addition, it appears that even if the hygiene procedures are followed, their effectiveness may be questionable because they are not properly executed. Studies show that hand washing takes on average 8-15 s [14][15][16]. This study confirms that the average time for washing hands is much shorter than it is required.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, it appears that even if the hygiene procedures are followed, their effectiveness may be questionable because they are not properly executed. Studies show that hand washing takes on average 8-15 s [14][15][16]. This study confirms that the average time for washing hands is much shorter than it is required.…”
Section: Discussionsupporting
confidence: 75%
“…The results of the univariate analysis indicate that the medi cal personnel adhered to the hand washing proce dures before contact with the patient only in 5.2% of the cases. This is a much lower proportion than the one re ported by other authors [11,[14][15][16][17][18]. According to the best knowledge of the authors, this is the only study using par ticipatory observation, in which the subjects, in addition to being ignorant of the true aim of the study, were intention ally diverted to the issues remote from the compliance with the principles of hygiene.…”
Section: Resultsmentioning
confidence: 78%
“…Observation-based studies revealed that the recommendation to use protective gloves was followed at the level of 58.8% [12]. The analysis of the results of our study showed that the overall level of compliance with the recommendation to use protective gloves in the circumstances that in accordance with the guidelines so require was 50%.…”
Section: Discussionmentioning
confidence: 60%